Suyanggae and her neighbours in Haifa, Israel : proceedings of the 20th (1) congress June 21-28, 2015 - Gonen, Sharon,; Ronen, Avraham, (Archaeopress Publishing Ltd, 2017)
The 20th symposium took place across two meetings, the first in Haifa, Israel and the second in Danyang, Republic of Korea. This proceedings volume gathers papers, abstracts and posters from the meeting in Haifa, which took place from 21-28 June 2015.